2009
DOI: 10.1128/jb.01130-08
|View full text |Cite
|
Sign up to set email alerts
|

Transforming DNA Uptake Gene Orthologs Do Not Mediate Spontaneous Plasmid Transformation in Escherichia coli

Abstract: Spontaneous plasmid transformation of Escherichia coli occurs on nutrient-containing agar plates. E. coli has also been reported to use double-stranded DNA (dsDNA) as a carbon source. The mechanism(s) of entry of exogenous dsDNA that allows plasmid establishment or the use of DNA as a nutrient remain(s) unknown. To further characterize plasmid transformation, we first documented the stimulation of transformation by agar and agarose. We provide evidence that stimulation is not due to agar contributing a supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Our further investigation revealed that plasmid transformation on plates is promoted by agar/agarose, a stimulation that is unrelated to divalent cations like Ca 2+ , Mg 2+ and Mn 2+ [10]. Interestingly, none of the DNA uptake gene homologs were found to be involved in mediating spontaneous plasmid transformation of E. coli [10]. The dose-response curve of transformation frequency as a function of DNA concentration showed that E. coli cells acquired plasmid DNA with a single hit kinetics, suggesting that plasmid DNA enters E. coli cells through a different route which allows double-stranded DNA (dsDNA) entry [10].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our further investigation revealed that plasmid transformation on plates is promoted by agar/agarose, a stimulation that is unrelated to divalent cations like Ca 2+ , Mg 2+ and Mn 2+ [10]. Interestingly, none of the DNA uptake gene homologs were found to be involved in mediating spontaneous plasmid transformation of E. coli [10]. The dose-response curve of transformation frequency as a function of DNA concentration showed that E. coli cells acquired plasmid DNA with a single hit kinetics, suggesting that plasmid DNA enters E. coli cells through a different route which allows double-stranded DNA (dsDNA) entry [10].…”
Section: Introductionmentioning
confidence: 77%
“…3) [10]. A recent report indicates that cell-to-cell transformation in E. coli may be regulated by a pheromone [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reannealing of complementary ssDNA fragments in the bacterial cytoplasm can theoretically occur (Saunders and Guild, 1981;Lorenz and Wackernagel, 1994;Domingues et al, 2012). Complementary DNA strands have been reported as dsDNA within the bacterial cell wall and within the transformed bacterial cell (Sun et al, 2009). …”
Section: (I) Exposure To Dnamentioning
confidence: 99%
“…Our previous research showed that E. coli could develop natural competence and take up plasmid DNA on agar plates in the absence of either additional Ca 2ϩ or heat shock (8). Furthermore, we found that DNA uptake gene orthologs required for other naturally transformable species were not involved in this transformation system (9), which implied that a different molecular mechanism of competence development and DNA uptake was being used. As reported by our group and others, the general stress response regulator RpoS ( S ) was shown to mediate natural transformation (10), and transformation frequencies were apparently increased when rpoS was induced in the liquid culture stage but did not change significantly when rpoS was induced on solid medium (11).…”
mentioning
confidence: 99%